Beyond MBBS: building a future worth staying for - Rehman, Sadia; Owais Saeed, Shaikh Muhammad; Tariq, Muhammad Ossama (Journal of the Pakistan Medical Association, 2026)
Dear Editor, The term brain drain refers to the emigration of highly trained professionals from their home countries to more developed nations, often in pursuit of better wages, career advancement, and an improved quality of life. (1) Between 1971 and 2022, a total of 6,019,888 highly qualified and skilled individuals migrated from the Pakistan. Among them, 50,110 (0.83%) were healthcare professionals, including 31,418 (62.69%), nurses 12,853 (25.64%), and pharmacists 5,839 (11.65%). (2) This increasing migration trend poses a serious threat to the healthcare infrastructure of Pakistan, where a shortage of trained professionals is already a pressing concern. In recent years, the migration of Pakistani medical professionals to high-income countries has reached unprecedented levels. In 2025, a major milestone was recorded when 1,061 Pakistani doctors secured residency positions in the United States—the highest number ever in a single year. (3) Many of these physicians were top graduates from some of Pakistan’s most prestigious medical institutions. The United States, however, is not the only destination attracting this talent. In 2023, the United Kingdom also experienced a significant influx, with over half (52%) of all non-UK medical graduates originating from just five countries—India, Pakistan, Nigeria, Egypt, and Bangladesh. Notably, Pakistan and Bangladesh ranked among the ten fastest-growing countries in terms of Primary Medical Qualification (PMQ) holders registering in the UK. (4) Australia, too, has reported a surge in interest from Pakistani-trained doctors. The Australian Medical Council’s 2023–24 Annual Report highlighted a marked increase in candidates from Pakistan attempting the AMC clinical examination, rising from 288 in 2022–23 to 500 in 2023–24. (5) These developments collectively underscore the growing exodus of skilled Pakistani medical professionals seeking better opportunities abroad, exacerbating the healthcare workforce gap at home. Pakistan’s healthcare system faces mounting challenges due to this persistent brain drain. Contributing factors include financial instability, lack of structured training programs, limited research opportunities, inadequate workplace safety, and political challenges. Despite the Pakistan’s diverse patient population and complex disease burden providing rich clinical exposure, these opportunities remain underutilized due to poor planning and resource constraints. To reverse this trajectory, investment in its medical workforce is essential. Competitive remuneration, transparent training pathways, research incentives, and improved workplace safety are critical to creating an environment where doctors feel valued and empowered. Such measures are necessary not only to retain medical talent but also to elevate the nation’s healthcare standards.